Composite positive pole piece, preparation method thereof and lithium ion battery

By designing a double-layer positive electrode active material layer in the positive electrode sheet of the lithium-ion battery, and introducing sulfide and oxide solid electrolyte to the outermost layer to cooperate, the problem of electrical performance degradation caused by solid electrolytes in lithium-ion batteries is solved, and the dual improvement of safety performance and electrical performance is achieved.

CN119725378APending Publication Date: 2025-03-28APOWER ELECTRONICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940501.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

After the introduction of solid electrolytes in existing semi-solid lithium-ion batteries, lithium ions migration is hindered, resulting in an increase in the internal resistance of the battery, affecting the conditions for large-scale use. At the same time, solid electrolytes have a great impact on electrical performance, making it difficult to take into account both safety performance and electrical performance.

Method used

A double-layer positive electrode active material layer is designed, and a sulfide solid electrolyte and oxide solid electrolyte are introduced into the outermost positive electrode active material layer to improve the safety performance and high and low temperature applicability of the battery, while promoting the rapid migration of lithium ions and reducing the impact of solid electrolytes on electrical performance.

Benefits of technology

It significantly improves the safety performance and high and low temperature applicability of the positive electrode sheet, reduces the impact of solid electrolyte on electrical performance, suppresses the heat diffusion rate of the battery, and achieves the dual improvement effect of safety performance and electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725378A_ABST
    Figure CN119725378A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive pole piece, a preparation method thereof and a lithium ion battery. The composite positive pole piece comprises: a positive current collector; the positive electrode active material layer is arranged on at least one side surface of the positive electrode current collector, and the positive electrode active material layer comprises a first positive electrode active material; the modified positive electrode active material layer is arranged on the surface of one side, far away from the positive electrode current collector, of the positive electrode active material layer, the modified positive electrode active material layer comprises a composite solid electrolyte and a second positive electrode active material, and the composite solid electrolyte comprises a sulfide solid electrolyte and an oxide solid electrolyte. The sulfide solid electrolyte and the oxide solid electrolyte are introduced to cooperate with each other, so that the safety performance and the high-low temperature applicability of the positive pole piece are remarkably improved, the influence of the solid electrolyte on the electrical performance is reduced, and the dual improvement effects of the safety performance and the electrical performance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a composite positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] For lithium-ion batteries, adding solid electrolytes to a liquid electrolyte that accounts for less than 10% can form a semi-solid battery. Adding solid electrolytes can solve the following problems: 1) Inhibiting the growth rate of lithium dendrites, and it is difficult for lithium dendrites to penetrate the solid electrolyte to cause a short circuit between the positive and negative electrodes; 2) In terms of flammability, the ignition point of the solid electrolyte is higher than that of the electrolyte, and the battery is not easy to catch fire; 3) In terms of thermal stability, the heat resistance limits of solid electrolytes with different compositions vary greatly (400-1800℃), but are significantly higher than the heat resistance limit of liquid battery separators (160℃), which can significantly improve the safety of the battery compared to liquid batteries; 4) The ionic conductivity of traditional electrolytes is greatly reduced at low temperatures, resulting in an increase in the internal resistance of the battery, while solid electrolytes can also maintain good conductivity at low temperatures, making them more advantageous for use under low temperature conditions; 5) Due to their good heat resistance, solid electrolytes do not volatilize or decompose at high temperatures, which can greatly increase the service life of the battery under high temperature conditions.

[0003] Therefore, adding solid electrolyte to form a semi-solid battery can effectively inhibit the growth rate of lithium dendrites. The ignition point is higher than that of the electrolyte battery, so it is not easy to catch fire and has strong heat resistance. It can significantly improve the safety issues caused by thermal runaway and the service life of the battery in high and low temperature states.

[0004] However, the existing technology has a single method for introducing solid electrolytes, which results in significantly increased resistance to lithium ion migration in the semi-solid battery, thereby increasing the internal resistance of the battery, inhibiting its charge and discharge rate, and being unfavorable for high-rate use conditions.

[0005] Therefore, how to improve the safety performance of the battery while reducing the impact of the solid electrolyte on the electrical performance to achieve a dual improvement in safety and electrical performance is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a composite positive electrode plate and a preparation method thereof and a lithium-ion battery. The present invention designs a double-layer positive electrode active material layer, and introduces a sulfide solid electrolyte and an oxide solid electrolyte in the outermost positive electrode active material layer for coordinated cooperation, which not only significantly improves the safety performance and high and low temperature applicability of the positive electrode plate, but also enables the lithium ions inside the battery to migrate quickly, which reduces the influence of the solid electrolyte on the electrical performance on the one hand, and suppresses the heat diffusion rate of the battery on the other hand, achieving a dual improvement effect of safety performance and electrical performance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a composite positive electrode sheet, the composite positive electrode sheet comprising:

[0009] Positive electrode current collector.

[0010] The positive electrode active material layer is disposed on at least one side surface of the positive electrode current collector, and the positive electrode active material layer includes a first positive electrode active material.

[0011] The modified positive electrode active material layer is arranged on the surface of the positive electrode active material layer on the side away from the positive electrode current collector. The modified positive electrode active material layer includes a composite solid electrolyte and a second positive electrode active material. The composite solid electrolyte includes a sulfide solid electrolyte and an oxide solid electrolyte.

[0012] The present invention designs a double-layer positive electrode active material layer and introduces a sulfide solid electrolyte and an oxide solid electrolyte in the outermost positive electrode active material layer for synergistic cooperation, which not only significantly improves the safety performance and high and low temperature applicability of the positive electrode plate, but also enables the rapid migration of lithium ions inside the battery, which, on the one hand, reduces the influence of the solid electrolyte on the electrical performance, and on the other hand, inhibits the heat diffusion rate of the battery, thereby achieving a dual improvement effect in safety performance and electrical performance.

[0013] The present invention introduces sulfide solid electrolyte and oxide solid electrolyte to cooperate with each other. Sulfide solid electrolyte can effectively improve the rate conductivity of the battery due to its good electrical conductivity, and oxide solid electrolyte can greatly improve the safety performance and high temperature performance of the battery due to its good stability and mechanical properties. The two work together to not only suppress the severity of the short-circuit reaction of the positive and negative active materials, increase the short-circuit internal resistance during the acupuncture process, prevent the temperature from rising, and improve the puncture pass rate of the lithium-ion battery; at the same time, when the battery is squeezed, the diaphragm shrinks due to heat, and the positive and negative electrodes are in contact, the battery's combustion can be reduced to avoid thermal runaway of the battery due to short circuit. In addition, the electrochemical performance of the battery can be improved more comprehensively.

[0014] It should be noted that the present invention does not limit the material of the positive electrode current collector, and illustratively, it can be aluminum foil, etc.

[0015] Preferably, the thickness ratio of the positive electrode active material layer and the modified positive electrode active material layer is (9-1):(1-9), wherein the selection range of the positive electrode active material layer "9-1" can be, for example, 1, 2, 3, 4, 5, 6, 7, 8 or 9, and the selection range of the modified positive electrode active material layer "1-9" can be, for example, 1, 2, 3, 4, 5, 6, 7, 8 or 9, and is preferably (1-3):(7-9).

[0016] In the present invention, the positive electrode active material layer and the modified positive electrode active material layer with a suitable thickness ratio can maximize the improvement of the safety performance and electrical performance of the battery.

[0017] Preferably, the mass ratio of the sulfide solid electrolyte to the oxide solid electrolyte is (2-8):(8-2), wherein the selection range of the sulfide solid electrolyte "2-8" can be, for example, 2, 3, 4, 5, 6, 7 or 8, and the selection range of the oxide solid electrolyte "8-2" can be, for example, 2, 3, 4, 5, 6, 7 or 8, and is preferably (4-6):(6-4).

[0018] In the present invention, the sulfide solid electrolyte and the oxide solid electrolyte in a suitable mass ratio can more comprehensively improve the electrical performance and safety performance of the battery.

[0019] Preferably, the first positive electrode active material and the second positive electrode active material each independently include any one of nickel-cobalt-manganese ternary, lithium manganese oxide, lithium iron phosphate or lithium cobalt oxide, or a combination of at least two thereof.

[0020] Preferably, the sulfide solid electrolyte includes Li 10 GeP2S 12 , Li 10 SiP2S 12 , Li2S-P2S5 or Li7P3S 11 Any one or a combination of at least two of the following.

[0021] Preferably, the oxide solid electrolyte includes any one of a garnet-type oxide solid electrolyte, a NASICON-type oxide solid electrolyte, a perovskite-type oxide solid electrolyte or a LiSICON-type oxide solid electrolyte, or a combination of at least two thereof.

[0022] Preferably, the garnet-type oxide solid electrolyte comprises Li7La3Zr2O 12 .

[0023] Preferably, the NASICON type oxide solid electrolyte comprises Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0024] Preferably, the perovskite oxide solid electrolyte comprises Li 0.33 La 0.56 TiO3.

[0025] Preferably, the LiSICON type oxide solid electrolyte comprises LiGa(SeO3)2.

[0026] In a second aspect, the present invention provides a method for preparing the composite positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:

[0027] The first positive electrode slurry is coated on at least one side of the positive electrode current collector, and a positive electrode active material layer is obtained after drying; wherein the first positive electrode slurry includes a first positive electrode active material.

[0028] The second positive electrode slurry is coated on the outer surface of the positive electrode active material layer, and the composite positive electrode plate is obtained after drying; wherein the second positive electrode slurry includes a composite solid electrolyte and a second positive electrode active material, and the composite solid electrolyte includes a sulfide solid electrolyte and an oxide solid electrolyte.

[0029] Preferably, the first positive electrode slurry further includes a first conductive agent, a first binder and a first solvent.

[0030] Preferably, the second positive electrode slurry further includes a second conductive agent, a second binder and a second solvent.

[0031] Preferably, the first conductive agent and the second conductive agent each independently include any one of conductive carbon black, acetylene black, carbon nanotubes, graphene or conductive graphite, or a combination of at least two thereof.

[0032] Preferably, the first binder and the second binder each independently include any one of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone or polyacrylonitrile, or a combination of at least two thereof.

[0033] The present invention does not limit the types of the first solvent and the second solvent. For example, they may be N-methylpyrrolidone, dimethylformamide, water or carbonate solvents.

[0034] Preferably, in the second positive electrode slurry, the mass proportion of the composite solid electrolyte is 2-6%, for example, it can be 2%, 3%, 4%, 5% or 6%.

[0035] Preferably, the method for preparing the second positive electrode slurry comprises the following steps:

[0036] The sulfide solid electrolyte and the oxide solid electrolyte are mixed, and then the obtained mixture is mixed with a second positive electrode active material, a second conductive agent, a second binder, and a second solvent to obtain the second positive electrode slurry.

[0037] Preferably, the coating methods of the first positive electrode slurry and the second positive electrode slurry each independently include any one of a doctor blade coating method, a slit die coating method, a screen printing coating method or a spray coating method.

[0038] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the composite positive electrode sheet as described in the first aspect.

[0039] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The present invention designs a double-layer positive electrode active material layer and introduces a sulfide solid electrolyte and an oxide solid electrolyte in the outermost positive electrode active material layer for synergistic cooperation, which not only significantly improves the safety performance and high and low temperature applicability of the positive electrode plate, but also enables the rapid migration of lithium ions inside the battery, which, on the one hand, reduces the influence of the solid electrolyte on the electrical performance, and on the other hand, inhibits the heat diffusion rate of the battery, thereby achieving a dual improvement effect in safety performance and electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic diagram of the structure of the composite positive electrode sheet provided in Example 1 of the present invention.

[0043] Among them, 1-positive electrode current collector; 2-positive electrode active material layer; 3-modified positive electrode active material layer. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] Example 1

[0046] This embodiment provides a composite positive electrode sheet, and its structural schematic diagram is as follows: Figure 1 As shown, the composite positive electrode plate comprises:

[0047] The positive electrode current collector 1 is aluminum foil.

[0048] The positive electrode active material layer 2 is disposed on both side surfaces of the positive electrode current collector 1 , and the positive electrode active material layer comprises a nickel-cobalt-manganese ternary material (NCM613), conductive carbon black and polyvinylidene fluoride.

[0049] The modified positive electrode active material layer 3 is arranged on the surface of the positive electrode active material layer 2 away from the positive electrode current collector 1, and the modified positive electrode active material layer 3 includes a composite solid electrolyte, a nickel-cobalt-manganese ternary material (NCM613), conductive carbon black and polyvinylidene fluoride. The composite solid electrolyte includes Li10 GeP2S 12 and Li7La3Zr2O 12 .

[0050] The thickness ratio of the positive electrode active material layer 2 to the modified positive electrode active material layer 3 is 3:7; Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 5:5;

[0051] This embodiment also provides a method for preparing the composite positive electrode sheet, the method comprising the following steps:

[0052] (1) NCM613, conductive carbon black and polyvinylidene fluoride were added into N-methylpyrrolidone solvent in a mass ratio of 98.4:0.8:0.8 to obtain a first positive electrode slurry, and then the first positive electrode slurry was scraped onto both sides of the positive electrode current collector, and dried to obtain a positive electrode active material layer.

[0053] (2) Li 10 GeP2S 12 and Li7La3Zr2O 12 The obtained mixture is mixed, and then the mixture and NCM613, conductive carbon black and polyvinylidene fluoride in a mass ratio of 98.4:0.8:0.8 are added to an N-methylpyrrolidone solvent to obtain a second positive electrode slurry, and then the second positive electrode slurry is scraped and coated on the outer surface of the positive electrode active material layer, and the composite positive electrode sheet is obtained after drying.

[0054] The mass proportion of the mixed material in the second positive electrode slurry is 4%.

[0055] Example 2

[0056] This embodiment provides a composite positive electrode plate, the composite positive electrode plate comprising:

[0057] The positive electrode current collector is aluminum foil.

[0058] The positive electrode active material layer is arranged on both side surfaces of the positive electrode current collector, and the positive electrode active material layer comprises NCM613, conductive carbon black and polyvinylidene fluoride.

[0059] A modified positive electrode active material layer is arranged on a surface of the positive electrode active material layer away from the positive electrode current collector, wherein the modified positive electrode active material layer comprises a composite solid electrolyte, NCM613, conductive carbon black and polyvinylidene fluoride, wherein the composite solid electrolyte comprises Li 10 SiP2S 12 and Li 1.3 Al 0.3Ti 1.7 (PO4)3.

[0060] The thickness ratio of the positive electrode active material layer to the modified positive electrode active material layer is 1:9; Li 10 SiP2S 12 and Li 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3 is 2:8;

[0061] This embodiment also provides a method for preparing the composite positive electrode sheet, the method comprising the following steps:

[0062] (1) NCM613, conductive carbon black and polyvinylidene fluoride were added into N-methylpyrrolidone solvent in a mass ratio of 98.4:0.8:0.8 to obtain a first positive electrode slurry, and then the first positive electrode slurry was scraped onto both sides of the positive electrode current collector, and dried to obtain a positive electrode active material layer.

[0063] (2) Li 10 SiP2S 12 and Li 1.3 Al 0.3 Ti 1.7 (PO4)3, and then add the obtained mixture and NCM613, conductive carbon black and polyvinylidene fluoride in a mass ratio of 98.4:0.8:0.8 into N-methylpyrrolidone solvent to obtain a second positive electrode slurry, and then scrape the second positive electrode slurry on the outer surface of the positive electrode active material layer, and obtain the composite positive electrode sheet after drying.

[0064] Wherein, the mass proportion of the mixed material in the second positive electrode slurry is 2%.

[0065] Example 3

[0066] This embodiment provides a composite positive electrode plate, the composite positive electrode plate comprising:

[0067] The positive electrode current collector is aluminum foil.

[0068] The positive electrode active material layer is arranged on both side surfaces of the positive electrode current collector, and the positive electrode active material layer comprises NCM613, conductive carbon black and polyvinylidene fluoride.

[0069] A modified positive electrode active material layer is arranged on a surface of the positive electrode active material layer away from the positive electrode current collector, wherein the modified positive electrode active material layer comprises a composite solid electrolyte, NCM613, conductive carbon black and polyvinylidene fluoride, wherein the composite solid electrolyte comprises Li7P3S 11 and Li 0.33 La0.56 TiO3.

[0070] The thickness ratio of the positive electrode active material layer to the modified positive electrode active material layer is 9:1; Li7P3S 11 and Li 0.33 La 0.56 The mass ratio of TiO3 is 8:2;

[0071] This embodiment also provides a method for preparing the composite positive electrode sheet, the method comprising the following steps:

[0072] (1) NCM613, conductive carbon black and polyvinylidene fluoride were added into N-methylpyrrolidone solvent in a mass ratio of 98.4:0.8:0.8 to obtain a first positive electrode slurry, and then the first positive electrode slurry was scraped onto both sides of the positive electrode current collector, and dried to obtain a positive electrode active material layer.

[0073] (2) Li7P3S 11 and Li 0.33 La 0.56 TiO3, and then add the obtained mixture and NCM613, conductive carbon black and polyvinylidene fluoride in a mass ratio of 98.4:0.8:0.8 into N-methylpyrrolidone solvent to obtain a second positive electrode slurry, and then scrape the second positive electrode slurry on the outer surface of the positive electrode active material layer, and obtain the composite positive electrode sheet after drying.

[0074] The mass proportion of the mixed material in the second positive electrode slurry is 6%.

[0075] Example 4

[0076] The difference between this embodiment and Embodiment 1 is that the thickness ratio of the positive electrode active material layer and the modified positive electrode active material layer is 9:1.

[0077] The rest of the preparation methods and parameters were the same as those in Example 1.

[0078] Example 5

[0079] The difference between this embodiment and Embodiment 1 is that the thickness ratio of the positive electrode active material layer and the modified positive electrode active material layer is 1:9.

[0080] The rest of the preparation methods and parameters were the same as those in Example 1.

[0081] Example 6

[0082] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 2:8.

[0083] The rest of the preparation methods and parameters were the same as those in Example 1.

[0084] Example 7

[0085] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 3:7.

[0086] The rest of the preparation methods and parameters were the same as those in Example 1.

[0087] Example 8

[0088] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 4:6.

[0089] The rest of the preparation methods and parameters were the same as those in Example 1.

[0090] Example 9

[0091] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 6:4.

[0092] The rest of the preparation methods and parameters were the same as those in Example 1.

[0093] Example 10

[0094] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 7:3.

[0095] The rest of the preparation methods and parameters were the same as those in Example 1.

[0096] Embodiment 11

[0097] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 8:2.

[0098] The rest of the preparation methods and parameters were the same as those in Example 1.

[0099] Example 12

[0100] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 1:9.

[0101] The rest of the preparation methods and parameters were the same as those in Example 1.

[0102] Embodiment 13

[0103] The difference between this embodiment and embodiment 1 is that Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio is 9:1.

[0104] The rest of the preparation methods and parameters were the same as those in Example 1.

[0105] Comparative Example 1

[0106] The difference between this comparative example and Example 1 is that the modified positive electrode active material layer does not contain Li 10 GeP2S 12 .

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] Comparative Example 2

[0109] The difference between this comparative example and Example 1 is that the modified positive electrode active material layer does not contain Li7La3Zr2O 12 .

[0110] The rest of the preparation methods and parameters were the same as those in Example 1.

[0111] Comparative Example 3

[0112] The difference between this comparative example and Example 1 is that no modified positive electrode active material layer is provided.

[0113] The rest of the preparation methods and parameters were the same as those in Example 1.

[0114] Performance Testing

[0115] A lithium-ion battery was assembled based on the composite positive electrode sheets provided in the above embodiments and comparative examples, and then the lithium-ion battery was subjected to electrochemical performance tests and safety performance tests.

[0116] For each embodiment and comparative example, 35 lithium-ion batteries are taken, of which 5 lithium-ion batteries are used for 1C rate discharge test at low temperature of -40°C, 5 lithium-ion batteries are used for 1C discharge test at low temperature of -20°C, 5 lithium-ion batteries are used for 85°C environmental storage test, and the remaining 20 lithium-ion batteries are used for puncture test (the above batteries need to be fully charged and tested at 100% SOC).

[0117] 1. Conduct low-temperature discharge performance and high-temperature storage performance tests. The test conditions are: 1C discharge at -40°C; 1C discharge at -20°C; storage at 85°C until gas expansion is ≤10%.

[0118] 2. Conduct safety performance test under the following conditions: ambient temperature of 20℃±5℃, relative humidity of (45-75)%RH. Specific test method includes: placing a lithium-ion battery with 100% SOC in a test slot of a needle puncture tester, puncturing the battery between the positive and negative electrodes to a depth of 3-5mm for 2-3s; inspecting the appearance of the lithium-ion battery after puncture, and recording the changes. If there is no fire or explosion, it is judged as qualified and recorded as PASS. If there is fire and / or explosion, it is judged as unqualified, i.e. NA.

[0119] The above test results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] analyze:

[0124] It can be seen from Example 1 and Examples 4-5 that if the thickness of the positive electrode active material layer and the modified positive electrode active material layer is relatively large, the high and low temperature performance of the battery will be poor and the needle puncture pass rate will be low; if the thickness of the positive electrode active material layer and the modified positive electrode active material layer is relatively small, although the performance is excellent, the improvement is not obvious.

[0125] It can be seen from Examples 1 and 6-13 that the greater the proportion of sulfide solid electrolyte in the composite solid electrolyte, the better the low-temperature discharge performance of the battery, but the high-temperature performance and needle puncture pass rate become lower, while the greater the proportion of oxide solid electrolyte, the higher the high-temperature storage performance and needle puncture pass rate of the battery, but the low-temperature discharge performance becomes worse. Therefore, while meeting the high and low temperature requirements, it also has high safety performance, so Li 10 GeP2S 12 and Li7La3Zr2O 12 The mass ratio of 4:6, 5:5 and 6:4 can maximize the high and low temperature electrical performance and safety performance of the battery.

[0126] It can be seen from Example 1 and Comparative Examples 1-2 that if the modified positive electrode active material layer does not contain Li 10 GeP2S 12 , it is not conducive to the battery to obtain excellent low-temperature discharge performance. If the modified positive electrode active material layer does not contain Li7La3Zr2O 12 , it is not conducive to the high-temperature storage of the battery and the improvement of the acupuncture safety performance.

[0127] It can be seen from Example 1 and Comparative Example 3 that if the modified positive electrode active material layer is not provided, the low temperature performance of the battery is extremely poor and it is difficult to use it in an ultra-low temperature harsh environment. It is also difficult to ensure the normal use of the battery under high temperature conditions, which may cause the battery to swell and bulge in severe cases. The safety performance of acupuncture is even more difficult to ensure, which may cause a series of safety fire accidents.

[0128] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite positive electrode sheet, characterized in that: The composite positive electrode sheet comprises: Positive electrode current collector; A positive electrode active material layer, disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a first positive electrode active material; The modified positive electrode active material layer is arranged on the surface of the positive electrode active material layer on the side away from the positive electrode current collector. The modified positive electrode active material layer includes a composite solid electrolyte and a second positive electrode active material. The composite solid electrolyte includes a sulfide solid electrolyte and an oxide solid electrolyte.

2. The composite positive electrode sheet according to claim 1, characterized in that: The thickness ratio of the positive electrode active material layer to the modified positive electrode active material layer is (9-1):(1-9), preferably (1-3):(7-9).

3. The composite positive electrode sheet according to claim 1 or 2, characterized in that: The mass ratio of the sulfide solid electrolyte to the oxide solid electrolyte is (2-8):(8-2), preferably (4-6):(6-4).

4. The composite positive electrode sheet according to any one of claims 1 to 3, characterized in that: The first positive electrode active material and the second positive electrode active material each independently include any one or a combination of at least two of nickel-cobalt-manganese ternary, lithium manganese oxide, lithium iron phosphate or lithium cobalt oxide; Preferably, the sulfide solid electrolyte includes Li 10 GeP2S 12 , Li 10 SiP2S 12 , Li2S-P2S5 or Li7P3S 11 Any one or a combination of at least two of the following: Preferably, the oxide solid electrolyte includes any one of a garnet-type oxide solid electrolyte, a NASICON-type oxide solid electrolyte, a perovskite-type oxide solid electrolyte or a LiSICON-type oxide solid electrolyte, or a combination of at least two thereof.

5. A method for preparing a composite positive electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Applying a first positive electrode slurry on at least one side of the positive electrode current collector, and drying to obtain a positive electrode active material layer; wherein the first positive electrode slurry includes a first positive electrode active material; The second positive electrode slurry is coated on the outer surface of the positive electrode active material layer, and the composite positive electrode plate is obtained after drying; wherein the second positive electrode slurry includes a composite solid electrolyte and a second positive electrode active material, and the composite solid electrolyte includes a sulfide solid electrolyte and an oxide solid electrolyte.

6. The preparation method according to claim 5, characterized in that: The first positive electrode slurry also includes a first conductive agent, a first binder and a first solvent; Preferably, the second positive electrode slurry further includes a second conductive agent, a second binder and a second solvent; Preferably, the first conductive agent and the second conductive agent each independently include any one or a combination of at least two of conductive carbon black, acetylene black, carbon nanotubes, graphene or conductive graphite; Preferably, the first binder and the second binder each independently include any one of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone or polyacrylonitrile, or a combination of at least two thereof.

7. The preparation method according to claim 5 or 6, characterized in that: In the second positive electrode slurry, the mass proportion of the composite solid electrolyte is 2-6%.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method of the second positive electrode slurry comprises the following steps: The sulfide solid electrolyte and the oxide solid electrolyte are mixed, and then the obtained mixture is mixed with a second positive electrode active material, a second conductive agent, a second binder, and a second solvent to obtain the second positive electrode slurry.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The coating methods of the first positive electrode slurry and the second positive electrode slurry each independently include any one of a doctor blade coating method, a slit die coating method, a screen printing coating method or a spray coating method.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite positive electrode sheet as described in any one of claims 1 to 4.